Vascular Impact of Cancer Therapies: The Case of BTK (Bruton Tyrosine Kinase) Inhibitors. Issue 12 (11th June 2021) - Fleming, Matthew R.; Xiao, Ling; Jackson, Klarissa D.; Beckman, Joshua A.; Barac, Ana; Moslehi, Javid J.
Abstract : Novel targeted cancer therapies have revolutionized oncology therapies, but these treatments can have cardiovascular complications, which include heterogeneous cardiac, metabolic, and vascular sequelae. Vascular side effects have emerged as important considerations in both cancer patients undergoing active treatment and cancer survivors. Here, we provide an overview of vascular effects of cancer therapies, focusing on small-molecule kinase inhibitors and specifically inhibitors of BTK (Bruton tyrosine kinase), which have revolutionized treatment and prognosis for B-cell malignancies. Cardiovascular side effects of BTK inhibitors include atrial fibrillation, increased risk of bleeding, and hypertension, with the former 2 especially providing a treatment challenge for the clinician. Cardiovascular complications of small-molecule kinase inhibitors can occur through either on-target (targeting intended target kinase) or off-target kinase inhibition. We will review these concepts and focus on the case of BTK inhibitors, highlight the emerging data suggesting an off-target effect that may provide insights into development of arrhythmias, specifically atrial fibrillation. We believe that cardiac and vascular sequelae of novel targeted cancer therapies can provide insights into human cardiovascular biology.